'I'd rather die happy': residents' experiences with food regulations, risk and food choice in residential aged care. A qualitative study. Issue 6 (2nd November 2017) - Bailey, Andrew; Bailey, Sherryn; Bernoth, Maree
Abstract : Background : Food regulations exist to protect older people in residential aged care, leading to the restriction of potentially hazardous foods. The impacts of malnutrition, resident centred care and the importance of maintaining individual autonomy for older people are well documented. By contrast, there is scant literature describing residents' perceptions of food regulations and food risks in the residential aged care setting. Aims : The aim of this study is to explore resident perceptions of food choice and food restrictions in residential aged care. Methods : Using a qualitative, hermeneutic phenomenological design, semi-structured interviews were conducted with six participants recruited from two residential aged care facilities. Interviews were audio-taped, transcribed verbatim and thematically analysed. Results : The following key themes emerged in this study: participants were largely unaware of food regulations and risks, yet expressed the desire to make their own choices. Participants provided contradictory accounts of their experiences with food in residential aged care, which emphasises the ongoing challenge of meeting individual preferences. Conclusion : These themes warrant further investigation, particularly in relation to the impact of food regulations on food choice and the meaning of risk to older people in residential aged care. This research provides new insight into the perceptions of residents regarding their individual autonomy and independence against legislated risk minimization strategies. Impact statement This article raises the issue of risk taking and food choices from the perspective of residents in a residential aged care facility.